1999
DOI: 10.1038/sj.jhh.1000884
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parental history of hypertension on blood pressure

Abstract: Aim: To assess the effect of parental history of hypertension on blood pressure in representative samples from three French populations (MONICA centres of Lille, Strasbourg, Toulouse). Methods: We screened 1660 males and 1635 females, aged 35-64 years. Subjects were defined as hypertensive if systolic blood pressure у160 mm Hg or diastolic blood pressure у95 mm Hg or if they were treated by antihypertensive drugs. Four groups of parental history were determined: no parental history; at least one parent hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
2
20
0
2
Order By: Relevance
“…Hahn et al reported that parental history was related to higher BP in females, but not in males, while Goldstein et al reported that elevated SBP and DBP measured by ambulatory monitoring was related to a family history of HT in both parents in males, but there was no association in females (21,22). It has also been reported that females tend to have a better knowledge of their own and their family's health status than males (23). Our findings indicate that females with a family history of HT were more likely to have high BP than males with a family history of HT.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hahn et al reported that parental history was related to higher BP in females, but not in males, while Goldstein et al reported that elevated SBP and DBP measured by ambulatory monitoring was related to a family history of HT in both parents in males, but there was no association in females (21,22). It has also been reported that females tend to have a better knowledge of their own and their family's health status than males (23). Our findings indicate that females with a family history of HT were more likely to have high BP than males with a family history of HT.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, when we analyzed determinants of pre-HT by dividing females into two groups, i.e., above or below the age of 50 years, determinants of pre-HT in the older females were BMI≥ 23 Determinants of HT (vs. NT) in males and females are shown in Table 3. Overweight and obesity were the strongest determinants of HT in comparison with NT.…”
Section: Resultsmentioning
confidence: 99%
“…A parent was identified as hypertensive if he/she was diagnosed with hypertension before the age of 60 and hypertension was present for at least 1 year. This procedure was followed because hypertension diagnosed in a parent after 60 years of age was not found to be a significant risk factor for the development of hypertension in offspring [17]. Parents had to have had a physical examination within the last year, knowledge of BP level, and, if pertinent, information on current antihypertensive status and medications.…”
Section: Subjectsmentioning
confidence: 99%
“…Also, this relationship depended on the age at which hypertension had been diagnosed in parents. 7 In the current study, multivariate analysis did not reveal any significant main effects of gender and parental history of hypertension alone and also no statistically significant interaction effect between the two.…”
Section: Discussionmentioning
confidence: 77%